Attitude of Hungarian companies towards challenges created by EU accession - Károly Balaton (Journal for East European Management Studies, 2005)
The paper analyses expectations and company strategies in relation to Hungary's joining the European Union. Data was collected from mainly medium-sized Hungarian companies by a questionnaire survey between January and April 2004. Companies perceived high level of uncertainty in relation to joining the EU. Many companies regard the accession as a possibility for expanding their business. Most of the respondents shared the view that after joining the Union competition would be increased and additional measures would be necessary to keep highly qualified work force. Preparing for the period after the accession can not be regarded as a primary strategic goal for the responding companies. This is partially explained by the fact that the sample includes companies mainly oriented toward the domestic market – – Der Aufsatz analysiert Erwartungen und Unternehmensstrategien in Relation zum EU-Beitritt. Daten wurden von hauptsächlich mittelgroßen ungarischen Unternehmen anhand einer Umfrage zwischen Januar und April 2004 erhoben. Unternehmen empfanden große Unsicherheit bezüglich dem EU-Beitritt. Viele Firmen sahen den Beitritt als eine Möglichkeit zur Geschäftserweiterung an. Die meisten Befragten teilten die Ansicht, dass nach einem Beitritt der Wettbewerb sich verstärken würde und dass weitere Maßnahmen nötig wären, um hochqualifizierte Arbeitskräfte zu erhalten. Die Vorbereitung auf die Zeit nach dem Beitritt ist keine primäres strategisches Ziel. Dies wird teilweise dadurch erklärt, dass von der Umfrage auch Unternehmen erfasst worden sind, die sich auf den auf den einheimischen Markt konzentrieren.
Keywords: 650; European Union; Hungary; competition; survey; domestic market